Perception of the population about the quality of life promoted by extensionist actions - Donizeti Alves Junior, Valdir; Barros Gutterres, Diogo; Reis Fonseca, Sávio; Almeida de Souza, Maria Cristina; Mendonça, Marcos Antônio (Guará Journal, 2017)
The project "The University Transformer in the community: small actions, great innovations!" (Assistance from the Foundation for Research Support of the State of Rio de Janeiro, FAPERJ), based on the social responsibility of Severino Sombra University (USS), en-abling the implementation of actions to prevent diseases, health education and basic assistance in Community of Ipiranga and Itakamosi neighborhoods, peripheral areas in Vassouras, State of Rio de Janeiro. Verify the community's perception towards extension activities is fundamental for organizational decision-making, aiming at internal improvement and betterment of actions, and also to identify needs that have not yet been met. Through a quantitative study, the perception of the residents about the impacts on their quality of life promoted by the project was evaluated. Data were collected through a structured instrument containing 12 questions (modified Servqual Scale), which addressed issues of satisfaction, trust, team responsibility, safety of project members, impact on quality of life and achievement of objectives. It was verified that the perception of the residents about the project is positive since their results generated impacts that qualified their lives positively. Thus, it was ratified the indispensability of university extension actions for the people's quality of life.